2014
DOI: 10.5603/fm.2014.0080
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atherosclerotic abdominal aorta on the shape of duplicated inferior vena cava: its potential clinical implications and vascular complications

Abstract: Duplication of the inferior vena cava (IVC) is a congenital condition (Folia Morphol 2014; 73, 4: 521-526)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…However, the presence of collaterals is indicative of ischemia development. Similar results were seen in syndromes which result from compression of veins by adjacent structures (Polguj et al, ; Orczyk et al, ). To demonstrate that fact, we managed to find a statistically significant correlation between range of CA stenosis and collateral network development.…”
Section: Discussionsupporting
confidence: 66%
“…However, the presence of collaterals is indicative of ischemia development. Similar results were seen in syndromes which result from compression of veins by adjacent structures (Polguj et al, ; Orczyk et al, ). To demonstrate that fact, we managed to find a statistically significant correlation between range of CA stenosis and collateral network development.…”
Section: Discussionsupporting
confidence: 66%
“…[10][11][12] Duplication of the IVC may be explained by numerous theories, such as persistence of the left IVC as a result of failure of the caudal left supracardinal vein to regress, or possibly a lack of anastomosis between primitive cardinal veins. 3,10 The development of renal veins is strongly connected with development of the IVC. 13 A research study concerning IVC anomalies, by Shin et al, 14 based the classification of double IVC subtypes on a previous study by Morita et al 15 Both studies suggested that there are five types of double IVC ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Unrecognised anomalies prior to medical procedures may lead to interruption of veins and severe haemorrhage. 3,4,6,8,9 To the best of the authors' knowledge, the present case is a unique description of duplicated IVC coexisting with nutcracker syndrome, presented using two complementary radiological techniques.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Duplicated veins are typically thin-walled, dilated, and even may be tortuous [8,17]. Such morphology may complicate surgical treatment and predispose the patient to unexpected bleeding.…”
Section: Duplication Of the Inferior Vena Cavamentioning
confidence: 99%